1989
DOI: 10.1055/s-0038-1647113
|View full text |Cite
|
Sign up to set email alerts
|

Is Quantitative Determination of Fibrin(ogen) Degradation Products and Thrombin-Antithrombin III Complexes Useful to Diagnose Deep Venous Thrombosis in Outpatients?

Abstract: SummaryWe studied the diagnostic value of recently introduced ELISA’s for the determination of thrombin-antithrombin III (TAT) complexes, fibrin degradation products (FbDP), fibrinogen degradation products (FgDP) and total degradation products (TDP) for deep venous thrombosis (DVT) in plasma of 239 consecutive outpatients, suspected for DVT by their family doctor. DVT was confirmed by impedance plethysmography in 60 patients. Using the 95th percentile range of 42 healthy volunteers the sensitivity for the dete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
13
2

Year Published

1991
1991
2016
2016

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 12 publications
3
13
2
Order By: Relevance
“…However, our study confirms the low sensitivity found by others [11,[19][20][21]. It was pointed out that the TAT values were higher when determined within 7 days after the onset of clinical symptoms [20], but we did not make the same observation (table 4), nor did Boneu et al [11].…”
Section: Discussioncontrasting
confidence: 40%
“…However, our study confirms the low sensitivity found by others [11,[19][20][21]. It was pointed out that the TAT values were higher when determined within 7 days after the onset of clinical symptoms [20], but we did not make the same observation (table 4), nor did Boneu et al [11].…”
Section: Discussioncontrasting
confidence: 40%
“…5 -611 It remains unclear why we did not find a significant difference in TAT levels when comparing the acute TIA group with either of the comparison groups. One possibility is that TAT lacks sensitivity as a marker of thrombin activation as suggested by Van Bergen et al, 20 who reported a sensitivity of only 50% in patients with deep vein thrombosis. It is not surprising then that sensitivity should also be low in TIAs where clot volume is much smaller than in deep vein thrombosis.…”
Section: Discussionmentioning
confidence: 93%
“…Other recently developed laboratory tests, like the assays for thrombin-antithrombin (TAT) complexes [32,39] and the assays for cross-linked and non-cross-linked fibrin deg radation products (FbDP EIA), for the total of fibrin and fibrinogen degradation prod ucts (TDP EIA) and for fibrinogen degrada tion products (FgDP EIA) have also been evaluated in the diagnosis of DVT [32], Nei ther of these assays reached a negative pre dictive value of 100%, although it should be noticed that the test characteristics of the EIAs for FbDP. TDP and FgDP have not yet been determined using ascending venog raphy in patients suspected of having DVT.…”
Section: Discussionmentioning
confidence: 99%
“…The same group of pa tients has been used to determine the test characteris tics of the assays for thrombin-antithrombin III (TAT) complexes, cross-linked and non-cross-linked fibrin degradation products (EIA for FbDP). fibrino gen degradation products (EIA for FgDP) and the total degradation products of fibrin and fibrinogen (EIA for TDP) [32]. Informed consent was obtained from each patient before IPG was performed and a venous blood sample was drawn.…”
Section: Methodsmentioning
confidence: 99%